The Metabolic Syndrome and Chronic Liver Disease - Rosselli, Matteo; Lotersztajn, Sophie; Vizzutti, Francesco; Arena, Umberto; Pinzani, Massimo; Marra, Fabio (Current Pharmaceutical Design, 2014)
The prevalence of the metabolic syndrome (MetS), a cluster of cardiovascular risk factors associated with obesity and insulin resistance, is dramatically increasing in Western and developing countries. This disorder is not only associated with a higher risk of appearance of type 2 diabetes and cardiovascular events, but impacts on the liver in different ways. Nonalcoholic fatty liver disease (NAFLD) is considered the hepatic manifestation of MetS, and is characterized by triglyceride accumulation and a variable degree of hepatic injury, inflammation, and repair. In the presence of significant hepatocellular injury and inflammation, the picture is defined ‘nonalcoholic steatohepatitis’ (NASH), that has the potential to progress to advanced fibrosis and cirrhosis. Diagnosis of NASH is based on a liver biopsy, and active search for noninvasive tests is ongoing. Progression of steatohepatitis to advanced fibrosis or cirrhosis has been shown in at least one third of patients followed with paired biopsies. Presence of NASH is associated with lower life expectancy, both due to liver-related death and to an increase in cardiovascular events. The appearance of NAFLD is mainly dependent on increased flow of fatty acids derived from an excess of lipolysis from insulin-resistant adipose tissue. Development of NASH is based on lipotoxicity and is influenced by signals derived from outside the liver and from intrahepatic activation of inflammatory and fibrogenic pathways. The presence of the MetS is also associated with worse outcomes in patients with cirrhosis due to any causes, and has complex interactions with hepatitis C virus infection. Moreover, MetS poses a higher risk of development of hepatocellular carcinoma, not necessarily through the development of NASH-related cirrhosis. In conclusion, the presence of metabolic alterations has a severe and multifaceted impact on the liver, and is responsible for a higher risk of liver-dependent and –independent mortality.
Keywords: Metabolic syndrome